Die Zyklik der Profite in der Ernährungswirtschaft: Ein internationaler Vergleich; Determinants of price-cost-margins over the business cycle for food industries: An international comparison - Julia Kor̈ner; Christoph Weiss (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– Based upon the structure-conduct-performance approach the present paper analyses determinants of price-cost-margins over the business cycle for food industries in Germany, the USA as well as the Netherlands. Controlling for market structure variables, cyclical fluctuations in profitability are interpreted as evidence for changes in firm behaviour. The econometric panel data models reveal pro-cyclic fluctuations of profits in highly concentrated industries in Germany. In contrast, profitability in competitive industries in Germany as well as in all US food industries are found to be more stable over the business cycle. This observation is explicable in terms of a more aggressive behaviour of firms in boom periods. The econometric model does not adequately explain industry differences in profitability in the Netherlands.
Keywords: 330; Ernährungsindustrie; Konjunktur; Gewinn; Vergleich; Deutschland; USA; Niederlande